(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
This article looks at the role and place of ideology in planning. The history of the concept of ideology is explained as well as the role that ideology plays in society. Ideology is not only present in science, but it is very important to realise this fact. Especially in planning this is very important, as no decision can be made in isolation. The concept of Urbanistics (as developed by Goudappel) is therefore a most helpful tool to be able to recognise the influence of ideology in the practice of planning. The three levels that Goudappel use to divide reflextion (thinking) into (infrastructure, suprastructure and ideostructure) are related to the questions what, how and why in planning practice. The highest level (ideostructure or the ‘why’ question) is where ideology is applicable, but in planning this level is often forgotten. In conclusion this article explains why this level is so important to take into consideration, as no decisions in planning can be free of the influence of ideology.